(untitled) (The Research of Medical Science Review, 2025)
Background: The ectopic pregnancy (EP) is the pregnancy that implant outside of the uterus, most commonly occur in the fallopian tube. The ampullary part of the tube is the commonest site. The pain and the bleeding are the common finding during EP. The use of IUD leads to EP. The pervious EP and tubal surgery is also responsible for EP. Trans-vaginal ultrasonography (TVS) is used for the confirmation of EP. Objectives: To determine the frequency of ectopic pregnancy at LRH. Methods: This cross sectional study was conducted in Gynae ultrasound section of LRH Radiology Department. This duration of study was four months i.e. from March 2019 to June 2019.The patients from LRH is included in this study based on convenient sampling technique. The data was collected through a standard Performa and was analyzed through SPSS 23. Results: 32 patients with EP are come to LRH. The pain and the bleeding are the most common finding. About 46.90% were come with second Gravidal status. Conclusion: The tubal pregnancy is most common among other pregnancies. The ampullary part is the commonest site to occur. The main reason for EP is the impair tube or ligated tube due to the tubal surgery.